Fitness effects of new mutations and adaptive evolution in house mice - Kousathanas, Athanasios (The University of Edinburgh, 2013)
Knowledge of the distribution of fitness effects of new mutations (DFE) can enable us to quantify the amount of genetic change between species that is driven by natural selection and contributes to adaptive evolution. The primary focus of this thesis is the study of methods to infer the DFE and the study of adaptive evolution in the house mouse subspecies Mus musculus castaneus. Firstly, I extended previous methodology to model the DFE based on polymorphism data. Methods that have previously been used to infer the DFE from polymorphism data have relied on the assumption of a unimodal distribution. I developed new models that can be used to fit DFEs of arbitrary complexity, and found that multimodality can be detected by these models given enough data. I used these new models to analyse polymorphism data from Drosophila melanogaster and M. m. castaneus, and found evidence for a unimodal DFE for D. melanogaster and a bimodal DFE for M. m. castaneus. Secondly, I investigated the contribution of change in coding and non-coding DNA to evolutionary adaptation. I used a polymorphism dataset of ~80 loci from M. m. castaneus sequenced in 15 individuals to investigate selection in protein-coding genes and putatively regulatory DNA close to these genes. I found that, although protein-coding genes are much more selectively constrained than non-coding DNA, they experience similar rates of adaptive substitution. These results suggest that change in functional non-coding DNA sequences might be as important as protein-coding genes to evolutionary adaptation. Thirdly, I used whole genome data from 10 M. m. castaneus individuals to compare the rate of adaptive substitution in autosomal and X-linked genes. I found that, on average, X-linked genes have a 1.8 times faster rate of adaptive substitution than autosomal genes. I also found that faster-X evolution is more pronounced for male-specific genes. I used previously developed theory to show that these observations can be explained if new advantageous mutations are recessive, with an average dominance coefficient less than or equal to 0.25. These results can help to explain the long-studied phenomenon of the large effect of the X chromosome in speciation.
Keywords: house mice; adaptive evolution; X chromosome; fitness effects